Intake of cocoa products and risk of type-2 diabetes: the multiethnic cohort - Maskarinec, Gertraud; Jacobs, Simone (European journal of clinical nutrition, 2019)
As cocoa products may be protective against chronic disease due to their polyphenol content, the current study determined the association of chocolate consumption and flavanol intake with type-2 diabetes (T2D) incidence in the Multiethnic Cohort (MEC) Study. The analysis included 151,691 participants of Native Hawaiian, Japanese American, Latino, African American, and white ancestry with 8487 incident T2D cases after 7.8 ± 3.5 years of follow-up. T2D status was based on three self-reports and confirmed by at least one of three administrative data sources. Dietary intake was assessed using a validated quantitative food frequency questionnaire, and flavanols from cocoa products were estimated from self-reported consumption of chocolate candy and drinks. Cox hazard regression, adjusted for potential confounders was applied to estimate hazard ratios (HR) and 95% confidence intervals (CI). For chocolate candy, both the highest vs. lowest (≥10 vs. <1 g/day) consumption (HR = 0.90; 95% CI, 0.83-0.97; ptrend = 0.01) and the frequency (≥4/week vs. <1/month) of intake (HR = 0.81; 95% CI, 0.72-0.91; ptrend = 0.0002) were inversely associated with T2D. The estimated flavanol intake from cocoa products (≥3 vs. <1 mg/day) also showed an inverse association with T2D risk (HR = 0.93; 95% CI, 0.88-0.99; ptrend = 0.02). Significant interaction terms indicated that the inverse relation was limited to Japanese Americans, normal-weight individuals, and to those without comorbidities. The current study confirms previous reports that participants with high intake of chocolate products and cocoa-derived flavanols experience a reduced risk of developing T2D even after controlling for sugar intake, diet quality, and other aspects of the diet.
Published: 24 May 2018
Gesehen am 15.07.2019